2002
DOI: 10.1046/j.1365-2362.2002.0320s1091.x
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 1 replication inhibition by the bidentate iron chelators CP502 and CP511 is caused by proliferation inhibition and the onset of apoptosis

Abstract: Iron chelators with high affinities for iron, which are under development for the treatment of iron overload, could contribute to the reduction of HIV-1 replication in infected patients by cellular proliferation inhibition rather than by a direct antiviral action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 21 publications
(29 reference statements)
1
25
0
Order By: Relevance
“…DFO and L1 are ideal candidates for use during in vitro analysis of co-infection and excess iron situations because they have already been implicated in HIV replication inhibition [8,[23][24]. DFO has also been successfully tested as inhibitor of mycobacterium infections [25] even though desferri-exochelins (siderophores secreted by M.tb) were able to inhibit DNA replication and ribonucleotide reductase activity at lower concentrations than the former chelator.…”
Section: Iron Chelatorsmentioning
confidence: 99%
“…DFO and L1 are ideal candidates for use during in vitro analysis of co-infection and excess iron situations because they have already been implicated in HIV replication inhibition [8,[23][24]. DFO has also been successfully tested as inhibitor of mycobacterium infections [25] even though desferri-exochelins (siderophores secreted by M.tb) were able to inhibit DNA replication and ribonucleotide reductase activity at lower concentrations than the former chelator.…”
Section: Iron Chelatorsmentioning
confidence: 99%
“…Several studies have demonstrated the potential of iron chelators in inhibiting HIV replication (Georgiou et al, 2000(Georgiou et al, , 2002Traoré and Meyer, 2004). In cultured T cells, excess iron stimulates HIV-1 viral replication, whereas iron chelation with desferrioxamine (DFO) lowers viral replication, as measured by decreased p24 levels and reverse transcriptase (RT) activity (Traoré and Meyer, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of monocyte-derived macrophages and peripheral blood lymphocytes with one of two chelators (DFO or deferiprone) reduced p24 expression and inhibited cellular proliferation (Georgiou et al, 2000). The orally active bidentate chelators 1,6-dimethyl-3-hydroxy-4-(1H)-pyridinone-2-carboxy-(N-methyl)-amide hydrochloride (CP502) and 6-dimethyl-3-hydroxy-4-(1H)-pyridinone-2-carboxy-(N-methyl)-amide hydrochloride (CP511) decreased HIV-1 replication and cellular proliferation in a manner similar to that of DFO and deferiprone (Georgiou et al, 2002). Thus, the observed reduction of HIV-1 replication by these chelators may reflect inhibition of cellular proliferation rather than inhibition of a specific host cell factor involved in HIV-1 replication.…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-3 has been shown to be involved in iron chelator-mediated apoptosis of human immunodeficiency virus type 1-infected peripheral blood lymphocytes (Georgiou et al, 2002) and teratocarcinoma F9 cells (Ido et al, 1999). In addition, it has been reported recently that induction of apoptosis by the iron chelator tachpyridine is characterized by early activation of caspase-9, followed by sequential activation of caspase-3 and caspase-8 (Greene et al, 2002).…”
Section: Introductionmentioning
confidence: 99%